The Effect of Using Structured Sports Video Media on Improving Basic Movement Skills of Students at SDN 7 Salotungo - Bahar, Awaluddin (Sains Global Institut, Indonesia, 2025)
This study aims to determine the effect of the use of structured sports video media on improving students' basic movements at SDN 7 Salotungo. This type of research is a quasi-experimental design with a population of all students in grades III and IV totaling 120 students. The research sample was 60 students divided into two groups, namely the experimental group and the control group, each with 30 students. The research instrument used a basic movement test that included walking, running, jumping, and throwing. Data analysis used an independent t-test with a significance level of 0.05. The results showed that there was a significant difference between the experimental group and the control group in improving students' basic movements (p <0.05). The average increase in basic movement scores in the experimental group was 28.5%, while the control group only increased by 8.2%. In conclusion, the use of structured sports video media has been proven effective in improving elementary school students' basic movements.